An overview of Islamization of knowledge from the perspective of International Institute of Islamic Thought’s (IIIT) - Laluddin, Hayatullah; Tahir, Ibrahim Nuhu (Scholars Academic and Scientific Publishers, 2018)
The Islamization of knowledge since its inception in the second half of 1970 has attracted the interest of Muslim intellectuals and activists throughout the world. It is a highly debated contemporary issue especially among the academia.Two academic Institutions spearhead the process; the International Institute of Islamic Thought and Civilization (ISTAC) and the International Institute of Islamic Thought (IIIT). This article attempts to examine the process from the IIIT perspective, due to its tremendous efforts in promotion and dissemination of the process by means of publication, seminars and workshops. A conceptual analysis of the process and its historical background is also dealt with in this paper. Some pioneers‟ view from the IIIT group and their strategy for Islamization of knowledge and their road-map for the process are also delineated. Using an analytical approach the article concludes the urgency of the need for the designation of an Islamic paradigm of knowledge based on the Islamic world view, by means of which Islamic intellectual heritage can be reactivated.